Nutrient and residue management in zero tilled-direct seeded basmati rice (Oryza sativa)-wheat (Triticum aestivum) system - KUMAR, PARVEEN; KUMAR, ASHWANI; RAI, A K; YADAV, R K; DAMODARAN, T; SHARMA, D K (The Indian Journal of Agricultural Sciences, 2021)
To assess the effect of nutrient and residue management on the performance of zero till - direct seed rice (DSR) (Oryza sativa L.)-wheat (Triticum aestivum L.) cropping system in partially reclaimed sodic soils, a three-year field experiment was conducted at ICAR-CSSRI during kharif and rabi 2016-18. The experiment was conducted in factorial randomized block design with 8 nutrient management options as first factor and two levels of residue management as second factor with three replications. Plant height, number of tillers and effective tillers were not affected significantly both in rice and wheat due to different nutrient and residue management treatments. Under different N management practices, basmati CSR 30 showed higher physiological efficiency in terms of SPAD reading, relative water content (RWC) and photosynthetic traits under treatments with recommended dose of fertilizers (RDF) + CSR bioformulation and RDF + CSR bioformulation + top cut at 75 days after sowing. Grain yield of basmati CSR 30 was the highest under transplanted conditions (36.0 q/ha) which was 20.0-30.6% higher than different nutrient and residue management treatments under DSR. Additional Zn application and foliar Fe sprays did not increase grain yield than RDF under ZT-DSR. Residual effect of nutrient and residue management was non-significant for all the yield attributes of wheat, viz. ear length, grains/ear and 1000-grain weight as well as for grain and straw yield of wheat. This study concludes that ZT-DSR is not suitable option for replacing puddled transplanted rice.